Effect of surface nanostructuring on corrosion behavior of Ti–6Al–4V alloy - Kumar S.; Chattopadhyay K.; Singh V. (My University, 2025)
Surface nanostructure was induced in Ti–6Al–4V alloy by ultrasonic shot peening (USSP) for different durations, from 15 s to 30 min, and the modified surface was characterized by optical, scanning, atomic force and transmission electron microscopy. Nano size grains were observed to form on surface of the USSPed samples and surface roughness was increased with duration of USSP. Polarization study was carried out in Ringer's solution to examine the effect of surface nanostructuring on corrosion resistance of this alloy. Electrochemical corrosion was carried out for all the USSPed specimens as well as the non-USSPed sample in Ringer's solution. Surface morphology of the corroded samples was examined by SEM. In general, corrosion resistance was improved by USSP up to the duration of 15 min and there was maximum improvement in the specimen USSPed for 1 min. However, corrosion resistance was drastically reduced due to USSP for long duration of 30 min. © 2016 Elsevier Inc.